Synthesis and Photocatalytic Activity Test of Bi-TiO2 toward Humic Acid Degradation under Visible Light Irradiation - Dien, Efraime Caroline; Aritonang, Anthoni Batahan; Gusrizal, Gusrizal (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
Humic acid (HA) in water can harm humans if it is regularly used or consumed. HA causes problems in the water, such as color, taste, and the formation of metal complexes. Therefore, it is necessary to degrade HA to address these problems. In this study, HA degradation was carried out using bismuth-doped TiO2 (Bi-TiO2) as a photocatalyst. The effect of Bi-TiO2 synthesized at various Bi concentrations and calcination temperatures on HA degradation was investigated and compared to pristine TiO2. Bi-TiO2 was synthesized via the sol-gel method and characterized using X-Ray Diffraction (XRD), Diffuse Reflectance Spectroscopy UV-Visible (DRS UV-Vis), and Fourrier Transform-Infra Red (FT-IR) Spectroscopy. The XRD analysis showed that the optimum calcination temperature was 500oC, with the highest crystallinity index (62.04%) and smallest crystallite size (11.95 nm). The DRS UV-Vis analysis showed that Bi-TiO2 1.5% led to the lowest band gap of 1.59 eV (λ = 782.33 nm), indicating that the photocatalyst was active under visible light irradiation. The FT-IR analysis showed an adsorption peak from the Bi-O bond at 802.39 cm-1, which caused a shift in the Ti-O-Ti adsorption peak. The photodegradation test was conducted using a 30 mL volume of HA solution 50 ppm and a 50 mg mass of catalyst. The results showed that Bi-TiO2 1.5% exhibited the highest efficiency in degrading HA, achieving 68.54% under visible light irradiation for 180 minutes. These results suggest the potential of Bi-TiO2 as an alternative method for treating HA in peat water using visible light irradiation.